Efficacy of acupuncture for psychogenic erectile dysfunction: a randomized, sham-controlled trial - Hao Wang; Xulu Lei; Dongyue Ma; Ziwei Zhao; Anmin Wang; Guanchao Du; Jiwei Zhang; Fu Wang; Jun Guo (Basic and Clinical Andrology, 2023)
Abstract Background Psychogenic erectile dysfunction (pED) is a common sexual dysfunction often accompanied by psychosomatic factors. Its treatment includes oral medications, psychotherapy, and behavioral therapy. Acupuncture’s effect on erectile function in pED patients remains to be investigated. This randomized study evaluated the effects of acupuncture and sham acupuncture in pED patients. Altogether, 66 men with pED were randomized to the acupuncture (n = 33) or sham acupuncture group (n = 33). Both groups have a 6-week treatment with 18 sessions. Primary outcome was the International Index of Erectile Function-5 (IIEF-5) at 6 weeks. Secondary outcomes were IIEF-5 (weeks 2, 4, and 10), erection hardness score (EHS), sexual encounter profile-2 (SEP-2), SEP-3, self-rating anxiety scale (SAS), and self-rating depression scale (SDS). Results Among the 66 participants, 64 completed the outcome measurements at week 10. Both acupuncture and sham acupuncture groups had improved IIEF-5 and EHS and decreased SAS and SDS post-treatment (p < 0.05). The acupuncture group had significantly better improvement in IIEF-5, EHS, and SEP-3 and significantly reduced SAS and SDS than the sham acupuncture group (p < 0.05). The improvement in SEP-2 post-treatment was not significantly different between the two groups (p > 0.05). There were no serious adverse events. Conclusions The 6-week acupuncture treatment significantly improved the erectile capacity and psychosomatic status of pED patients. Trial registration ChiCTR2200064345 (Chinese Clinical Trial Registry) ( https://www.chictr.org.cn/showproj.html?proj=174873 ).